Efektivitas Pemberian Modalitas Fisioterapi TENS, Stretching, dan Strengthening pada Kasus Trigger Finger Digiti III Dextra - Putri Nadzifatun Tri Maghfuroh; Atika Yulianti (Lembaga Pengembangan Kinerja Dosen, 2025)
Trigger finger is a condition where the flexor tendons stiffen from excess pressure, causing pain, stiffness, and limited range of motion when straightening a bent finger. The purpose of this study was to evaluate the effects of three weeks of physiotherapy interventions, including TENS, massage, stretching, and strengthening, on patient recovery. One patient with trigger finger disease in the right third digiti was the subject of this case study. The results obtained were a decrease in pain on movement T0: 9 to T2: 6, pain on pressure T0: 8 to T2: 5, an increase in the strength of the right wrist and hand muscles from T0: 3 to T2: 4 and the left part from T0: 4 to T2: 5, and an increase in the range of motion of the metacarpohalangeal joint of the right finger III from T0: S = 30 ̊ - 0 ̊ - 50 ̊ to T2: S = 30 ̊ - 0 ̊ - 60 ̊ and the proximal interphalangeal of the right finger III from T0: S = 0 ̊ - 0 ̊ - 90 ̊ to T2: S = 30 ̊ - 0 ̊ - 105 ̊. Thus, the provision of physiotherapy intervention to patient Mr. S is said to be effective in reducing the condition of the problem experienced.